Integrasi Profil Pelajar Pancasila dalam Pembelajaran PPKn untuk Meningkatkan Sikap Moral Siswa - Iqbal, Iqbal; Syafriadi, Syafriadi (Paedagogie, 2025)
National education in Indonesia is currently facing a serious challenge in the form of a gap between theoretical moral knowledge and students' actual behavior in the field. This study aims to analyze the integration strategy and effectiveness of the implementation of the Pancasila Student Profile in Pancasila and Citizenship Education (PPKn) learning to improve students' moral attitudes amidst the challenges of adolescent moral degradation. Using a descriptive qualitative approach, data collection was carried out through participatory observation, in-depth interviews with 3 teachers and 10 students, as well as documentation studies of teaching modules at SMP Negeri 1 Simpang Tiga, Pidie district, which were then analyzed using the interactive model of Miles, Huberman, and Saldana. The results showed that integration was carried out through three main strategies, namely the insertion of values ​​in teaching materials, a project-based learning model, and school culture habituation. In addition, a significant increase was found in students' moral attitudes, especially in the dimensions of faith and piety in the aspects of academic honesty, mutual cooperation in collaboration, and global diversity in tolerance. This study concludes that PPKn learning oriented on the Pancasila Student Profile is effective in transforming civic knowledge into real and relevant moral dispositions. Therefore, it is recommended that schools adopt Pembelajaran Berbasis Proyek as the main model and strengthen habituation as a support for the whole-school approach to character sustainability